Burroughs [videorecording (DVD)] - Brookner, Howard; Burroughs, William S., 1914-1997; Bacon, Francis, 1909-1992; Burroughs, William S., 1947-1981 (Criterion collection, 2015)
Made up of intimate, revelatory footage of the singular author and poet filmed over the course of five years, Howard Brookner's 1983 documentary about William S. Burroughs (Naked Lunch) was for decades mainly the stuff of legend; that changed when Aaron Brookner, the late director's nephew, discovered a print of it in 2011 and spearheaded a restoration. Includes on-screen appearances by Allen Ginsberg, Herbert Huncke, Terry Southern, and Lucien Carr.